Synergizing Solar Cell Technology, Radio Waves, AI, and Business: A Comprehensive Review - Alexandra Harry (Information Technology and Science (ITScience), 2023)
This thorough review article reveals the amazing possibilities for innovation, sustainability, and connectedness by examining the revolutionary synergy of solar cell technology, radio waves, artificial intelligence (AI), and business. A new era of possibilities has emerged from the merging of these dynamic sectors, ranging from using AI to optimize solar energy generation to utilizing 5G technology and the Internet of Things (IoT) to revolutionize wireless communication. These technologies' convergence provides an ideal environment for entrepreneurship, as demonstrated by successful examples like Verizon's 5G-enabled smart cities and Sun Power’s AI-enhanced solar panels. Although this convergence offers ground-breaking potential, it also brings with it difficult problems. These include the effective management of electromagnetic spectrum, ethical AI concerns, and regulatory difficulties. In order to effectively manage this constantly changing environment, stakeholders need to support international collaboration, STEM education, flexible regulatory frameworks, and interdisciplinary research. To fully realize the revolutionary potential of these technologies, workforce development, incentives for sustainable habits, and sustainable technology research are crucial. In addition, in order to spur innovation in green AI, energy-efficient wireless communication, and renewable energy, governments and organizations need to make investments in green technology. It is critical to comprehend the main lessons in light of the changing environment at the nexus of these dynamic disciplines. These include the necessity of inclusivity, the value of sustainability, and the importance of ethical AI. Adopting these tenets will direct us toward a future marked by continuous progress, convergence of technology, and a flourishing innovation environment. Lessons from this review article will act as a compass for people who want to create positive change, maximize synergy, and take advantage of the endless opportunities that lie ahead as we navigate this environment. By working together, we can build a more affluent, connected, and sustainable future for everybody.